Factores de riesgo y prevención para cáncer cervicouterino en mujeres de la Facultad de la Salud Humana de la Universidad Nacional de Loja - Alvarez Enríquez, Rosa María (2024)
Cervical cancer is the fourth cause of death in women worldwide, 570,000 are diagnosed each year, and the second cause in Ecuador. For the National Institute of Statistics and Census (INEC) during the years 2015 to 2020, 2,735 deaths and 10,011 cases of cervical cancer affecting women aged 40 to 64 years were registered. The purpose of the research was to determine the risk factors and prevention of cervical cancer in women of the Faculty of Human Health of the National University of Loja from December 2022 to March 2023. It was configured as a quantitative research of transversal cohort type, conformed by 395 women who fulfilled the inclusion and exclusion criteria, to whom an information collection sheet and a survey were applied. The results showed that 50.13% (n=198) were between 21 and 30 years of age, most of them students. The risk factors that prevailed were smoking and the initiation of sexual relations at an early age, multiple sexual partners in 7.09 (n=28), of which 17.72% (n=70) did not use contraceptives and 3.54% (n=14) registered multiparity. 32.15% (n=127) had their first Pap smear examination before the age of 25 years. The barriers to this examination were fear of the procedure in 24.25% (n=65) and as a factor favoring it was being part of a routine examination in 70.87% (n=90). It was concluded that the participants have a low culture of prevention with respect to cervical cancer